An exposure assessment approach for potential thermal degradation compounds in 2‐phase immersion cooling operations. Issue 3 (8th January 2018) - Tuma, Phillip; Schulz, Jay; Bonk, Jason; Roy, Robert; DeLorme, Michael; Logan, Perry
Abstract : Passive 2‐phase immersion cooling (P2PIC) is a technique for cooling computers with the potential to reduce capital and operating costs within datacenters. Computers cooled by P2PIC are submerged in a fluorochemical liquid that boils (hence 2‐phase) from the heat generating components. Although the tanks in which this is done are normally sealed and vented outdoors, they are opened periodically for maintenance. The volatility of the liquids suggests the need for risk assessments relating to inhalation of the liquids' vapor under these normal operating conditions. Fourier transfer infrared vapor concentration measurements gathered during spill and transfer simulation and at two proof‐of‐concept P2PIC installations show inhalation concentrations substantially below exposure guidelines. Liquids can be thermally decomposed under certain failure scenarios to create decomposition products with greater hazard and risk profiles. A methodology is presented for estimating possible human exposure to such products. The exposure levels that result are interpreted in the context of the most toxic of the thermal decomposition products known to form and suggest employee exposure substantially below published occupational exposure and emergency response guidelines. Fluid conditioning systems and gas monitoring equipment further reduce the risk of human exposure to fluid vapor and thermal decomposition products. © 2017 American Institute of Chemical Engineers Process Process Saf Prog 37:369–375, 2018